Expression of the AtSUC1 gene in the female gametophyte, and ecotype-specific expression differences in male reproductive organs. - Feuerstein, Andrea; Niedermeier, Matthias; Bauer, Katja; Engelmann, Sabine; Hoth, Stefan; Stadler, Ruth; Sauer, Norbert (Plant Biology, 2010)
Based on analyses in Arabidopsis thaliana ecotype C24, the AtSUC1 protein was previously characterised as a male gametophyte-specific H(+)/sucrose symporter. Later, expression analyses in ecotype Columbia-0 (Col-0) identified AtSUC1 expression also in trichomes (not detected in trichome-less C24 plants) and roots, suggesting ecotype-specific differences in AtSUC1 expression. Here, we present data on additional ecotype-specific differences in AtSUC1 expression in other tissues. Using different AtSUC1 promoter-reporter gene lines, we performed comparative analyses of AtSUC1 expression in floral tissues of C24 and Col-0 plants, and using an AtSUC1-specific antiserum, we performed immunohistochemical analyses on tissue sections from C24, Col-0, Landsberg erecta (Ler) and Wassilewskaija (Ws) ecotypes. We show that AtSUC1 expression occurs in the funicular epidermis of C24, Ler and Ws, but not in Col-0. In contrast, we observed high levels of AtSUC1 protein in pollen grains of Col-0, lower levels in pollen of C24 and Ler, and no AtSUC1 protein in Ws pollen. Moreover, our reporter gene analyses identified a previously undetected expression of AtSUC1 in the female gametophyte, and revealed that AtSUC1 expression in the funicular epidermis is absent from unpollinated siliques and is induced upon successful pollination. The impact of these findings on the potential physiological role of AtSUC1 is discussed.